Corpus Planning and Tri-Media Enhancement of Intellectualized Filipino for Mass Communication - Carpio, Perla; Carpio, Ricardo (Social Sciences and Development Review, 2019)
In the Philippines, education, history and topography dictated why the medium of communication in many fields including broadcast and print media is English. But when Filipino was constitutionalized in 1987, corpus planning in the national language has given of great importance by the Komisyon sa Wikang Filipino (KWF) to intellectualized and create a standardized jargon for mass communication. Though translated lexes were printed in Filipino books and taught in higher education institutions (HEIs.) there is no measure on the usability and acceptability of the lexes. Following Haugen’s and Ferguson’s language planning concepts this paper focused on the utilization importance of the lexes for mass communication as surveyed to students who undergone on-the-job training in different mass media channels. Focus group discussion as well as interview to experts of the fields corroborates facts found. Conclusion of the paper enumerated the lexes need to be revised to adapt with the needs of field: Corpus planning management need to be carefully designed to alleviate the status of the speakers’ own language instead of empowering a foreign language; the use of technology may be employed such as crowdsourcing, use of translation engines and other media platforms as well as word assimilation and adaptation and manual efforts for validation of the harvested and collected lexes; speakers maybe allowed to freely use whatever variety they may utilize to meet better understanding and usability of lexes; lastly, to propagate suggested lexes, language agencies, expert of the fields shall give importance on the production of books, publication of articles and researches on top of the use of Filipino in different fora and the like.
Keywords: Intellectualization; Language planning; lexicon; Corpus planning; standardization